Identification and distribution of SIFamide in the nervous system of the desert locust Schistocerca gregaria. Issue 1 (1st January 2015) - Gellerer, Alina; Franke, Aileen; Neupert, Susanne; Predel, Reinhard; Zhou, Xin; Liu, Shanlin; Reiher, Wencke; Wegener, Christian; Homberg, Uwe
ABSTRACT SIFamides are a family of highly conserved arthropod neuropeptides. To date, nine orthocopies from different arthropods, most of them insects, have been identified, all consisting of 11–12 amino acid residues. The striking conservation in sequence is mirrored by highly similar morphologies of SIFamide‐immunoreactive neurons: immunolabeling in various insect species revealed four immunopositive neurons with somata in the pars intercerebralis and arborizations extending throughout the brain and ventral nervous system. In contrast, the functional role of these neurons and their neuropeptide SIFamide is largely obscure. To provide an additional basis for functional analysis, we identified, by matrix‐assisted laser desorption/ionization time of flight (MALDI–TOF) mass spectrometry, a SIFamide peptide in the desert locust Schistocerca gregaria and studied its distribution throughout the nervous system. Identification was supported by analysis of transcriptomic data obtained from another grasshopper, Stenobothrus lineatus. Scg‐SIFamide, unlike all SIFamides identified so far, is a pentadecapeptide with an extended and highly modified N‐terminus (AAATFRRPPFNGSIFamide). As in other insects, pairs of descending neurons with somata in the pars intercerebralis and ramifications in most areas of the nervous system are SIFamide‐immunoreactive. In addition, a small number of local interneurons in the brain and ventral ganglia were immunostained. Double‐label experiments showed that the SIFamide‐immunoreactive descending neurons are identical to previously characterized primary commissure pioneer (PNP) neurons of the locust brain that pioneer the first commissure in the brain. The data suggest that the descending SIFamide‐immunoreactive neurons play a developmental role in organizing the insect central nervous system. J. Comp. Neurol. 523:108–125, 2015. © 2014 Wiley Periodicals, Inc.